Teachers’ Perception toward the Obstacles of E-Learning Classes - Sutri Windiarti; Nurul Fadilah; Eka Dhermawati; Bambang Widi Pratolo (Ethical Lingua: Journal of Language Teaching and Literature, 2019)
This study aims to describe the teacher's perception of the obstacles in the implementation of e-learning in the learning process and the recommendation to solve the problems. This research is a qualitative descriptive study. The research subjects were two teachers who taught at a University in Yogyakarta. The research data collected through in-depth interviews, which were analyzed descriptively by using interactive techniques. The Interactive analysis is done by collecting data, reducing data, presenting data, and drawing conclusions. The results of the data analysis show that two teachers were not too familiar with e-learning, so they still have many obstacles in the teaching process by using e-learning. There are several obstacles, such as obstacles in teaching by using e-learning as devices, teachers' knowledge, time management, and students ’motivation. In order to run e-learning entirely, then these obstacles should be solved first. There are two teachers suggest overcoming the obstacles, such as training for the teachers, and repairing the facilities of the institution.